Halal Industry in Uzbekistan: Analysis Using the Viable System Model - Khairul Akmaliah Adham; Adlin Masood; Nur Sa’adah Muhamad; Zizah Che Senik (Emerald Publishing Limited, 2024)
Indexed by WOS/Scopus/ERA